Knowledge, attitude and health seeking practice on bats-borne diseases among residents of Tioman Island, Malaysia - Mohamed N.A.; Said M.H.; Mohd Rani M.D.; Ramli S.; Isahak I. (Malaysian Society for Parasitology, 2024)
Indexed by WOS/Scopus/ERA